Pelatihan Pengolahan Ekstrak Albumin dan Pemanfaatan Hasil Sampingnya Di Desa Pal Batu Kecamatan Paminggir - Sari, Dewi Kartika; Khairina, Rita (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
The fishery sector is the mainstay in Paminggir District, one type of fish that is caught a lot is snakehead fish. So far, the use of snakehead fish is limited as fish consumption, so to increase the use of snakehead fish it is necessary to diversify the technology of processed snakehead fish into a product with higher nutritional and economic value. Community partnership program service activities aim to transfer technology through technical training on albumin extract processing and utilization of by-products. The training method is counseling and demonstration that aims to provide knowledge and skills to the target audience from Paminggir District, namely the people of Sungai Namang, Pal Batu, Bararawa and Tampakang Villages. The results of the training activities show that the snakehead fish processing business is starting to become a concern for the community in Paminggir District. The follow-up plan of the training activities is the formation of creative business development opportunities that lead to the formation of micro, small and medium enterprises (MSMEs) through empowering local communities by utilizing local potential, namely snakehead fish.